'The craft so long to lerne': aspects of time in language learning. Issue 3 (2nd September 2017) - Oxford, Rebecca L.
ABSTRACT: Time factors complexly, dynamically interact with each other and with other contextualized variables in language learning. The time-tied nature of language learning is captured in what I call the 'time-prism, ' which is the central symbol of temporality in this paper. The facets of the prism discussed in this article are (1) language learners' hope, agency, autonomy, and mindsets; (2) time as related to socioculturally mediated learning; (3) time as embodied in specific self-regulated task phases, complexity theory, and learning strategies; (4) diverse understandings of time perspectives (past, present, and future); (5) time, imagination, and motivation; and (6) time and emotions (affective time aspects).